Berlin evaluates school tobacco prevention - BEST prevention: study design and methodology - Müller-Riemenschneider, Falk (BioMed Central, 2014)
BACKGROUND: The hazardous health effects of smoking are established, but there remains a need to evaluate existing smoking prevention strategies and to increase their effectiveness in adolescents. Strategies focusing on parental attitudes and rule setting have been identified as a potentially effective approach. The present manuscript describes objectives, study design and methodology of the BEST Prevention study. METHODS/DESIGN: BEST Prevention is a three-armed cluster randomized-controlled trial among 7(th) grade (11–16 years) students in Berlin, Germany. Schools were enrolled between 2010 and 2011 and allocated using a centralized randomization list into 1) a student smoking prevention intervention (visit to an established interactive circuit), 2) the same intervention plus a parent intervention, and 3) a control group (visit to an established exercise and nutrition interactive circuit). Students were assessed at baseline, 12 and 24 months via self-report, as well as via carbon monoxide and cotinine in saliva at the 24 month follow-up. Statistical analyses uses multi-level regression models with cluster effects (school and class within school) based on the intention to treat population. Here we report descriptive baseline characteristics of recruited schools, and schools classes. Two schools from the control group dropped out after allocation. Hence, 47 secondary schools from all 12 districts of the city, including 161 school classes and 3023 students are participating in the study. Of those, 2801 students completed the baseline assessment. DISCUSSION: The present manuscript provides details on the study design and methodology of a large school-based smoking prevention trial in a metropolitan area in Germany. Findings from this study will yield important insight into the long-term effectiveness of specific smoking prevention strategies, also in disadvantaged population groups. TRIAL REGISTRATION: NCT01306552 (January 2011).